Analysis of the Sports Class Program for Sustainable Young Athlete Development: (A Case Study at Muhammadiyah 2 Junior High School, Surabaya) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to evaluate the effectiveness of the Sports Class Program at Muhammadiyah 2 Junior High School, Surabaya, as a model for sustainable early-age athlete development. The research focuses on analyzing the program's implementation and identifying the supporting and inhibiting factors in realizing the integration of academic education and intensive sports training. This study employs a qualitative method with a case study approach. Data were collected through in-depth interviews with various stakeholders, participant observation within the school environment, and a documentation study of the curriculum and program records. The findings indicate that the program has successfully implemented an integrated curriculum that balances academic demands and athletic training. This success is underpinned by the availability of competent coaches and a robust collaborative network with sports clubs. Conversely, the study also revealed significant challenges, namely the perceived dual burden on the student-athletes and limitations in supporting facilities. The findings of this study provide an important contribution to the development of the sports school model in Indonesia. This Sports Class Program can serve as a prototype that requires adaptation, with particular attention given to solutions for the identified challenges, such as athlete load management and facility provision. Consequently, this research recommends the necessity for stronger systemic support from policy stakeholders to ensure the sustainability and future replication of similar models.